Adsorption of hydrogen in Scandium/Titanium decorated nitrogen doped carbon nanotube - Mananghaya, Michael; Belo, Lawrence Phoa; Beltran, Arnel (Materials chemistry and physics, 2016)
Nitrogen doped Carbon Nanotube with divacancy (4ND-CNxNT) that is decorated with Scandium and Titanium as potential hydrogen storage medium using the pseudo potential density functional method was investigated. Highly localized states near the Fermi level, which are derived from the nitrogen defects, contribute to strong Sc and Ti bindings, which prevent metal aggregation and improve the material stability. A detailed Comparison of the Hydrogen adsorption capability with promising system-weight efficiency of Sc over Ti was elucidated when functionalized with 4ND-CNxNT. Finally, the (Sc/4ND)10-CNxCNT composite material has a thermodynamically favorable adsorption and consecutive adsorption energy for ideal reversible adsorption and desorption of hydrogen at room temperature such that it can hold at least 5.8 wt% hydrogen molecules at the LDA and GGA level. •Carbon Nanotube with divacancy (4ND-CNxNT) decorated with Sc and Ti.•Nitrogen defects, contribute to strong Sc and Ti bindings.•H2 and (Sc/4ND)10-CNxCNT has a favorable adsorption.•5.8 wt% adsorption at the LDA and GGA level.